The Use of the Polish Germplasm Collection of Nicotiana tabacum in Research and Tobacco Breeding for Disease Resistance - Anna Czubacka (Agriculture, 2022)
The Polish germplasm collection of Nicotiana tabacum was started in the 1920s. Up to now, more than eight hundred accessions originating from different regions of the world have been gathered in the collection. It includes valuable breeding lines and obsolete cultivars, among them cytoplasmic male-sterile lines. Numerous cultivars are rich sources of features desired in tobacco breeding. Therefore, the accessions are continually characterised in terms of their various features, one of the most important of which is disease resistance. Much research is being done to explain the nature of resistance and its genetic basis. Moreover, cultivars with good agronomic characteristics are used in wide hybridisation, being recipients of resistance genes from wild species or are genetically modified with transgenes conditioning resistance. The biological diversity of cultivars also allows a proper selection of plant material for pathogen studies, while the large number of the accessions facilitates research into the conditions for long seed storage. Numerous examples of the use of Polish tobacco germplasm in research and breeding, specifically in disease resistance, have been presented in this paper.